Narratives of Dreams and Waking Thoughts: Emotional Processing in Relation to the COVID-19 Pandemic - Mariani, Rachele; Gennaro, Alessandro; Monaco, Silvia; Di Trani, Michela; Salvatore, Sergio (Frontiers in Psychology, 2021)
The Coronavirus-19 (COVID-19) pandemic posed a significant challenge to the physical, mental, and emotional well-being of each individual. It also brought the importance of daily emotional management for survival to the forefront of every human being. Our study aims to explore whether emotional processes perform different functions during waking thoughts and night dreams during the first lockdown in Italy. Utilizing Multiple Code Theory, our goal is to verify whether waking thoughts facilitate a functional disconnection in order to manage the trauma caused by COVID-19. Two online forms were distributed to random participants in the general population, presenting a total of 49 reports of night dreams (23 males; mean age 33,45 ds. 10.12; word mean 238,54 ds. 146,8) and 48 reports of waking thoughts (25 males; mean age 34.54 ds. 12.8; word mean M. 91 words ds. 23). The Referential Process linguistic measures and Affect Salience Index were utilized. It was found that Affect Salience is present in both dreams and in waking thoughts; however, Referential Activity was higher in dreams and Reflection and Affect words were higher in waking thoughts. Two different processes of emotional elaboration emerged. The results highlight the use of greater symbolization processes during dreams and a higher emotional distance in waking thoughts. These results confirm that during the nocturnal processes, there is greater contact with the processing of trauma, while during the diurnal processes, defensive strategies were activated to cope with and manage life via a moment of the defensive disruption of daily activities.